Political connections and tax avoidance: The role of politically affiliated ownership in corporate tax strategies - Yusuf, Muhammad; Ismail, Tubagus; Taqi, Muhammad; Soleha, Nurhayati (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of political connections on tax avoidance in Indonesian State-Owned Enterprises (SOEs) from 2019 to 2024. Using panel data regression analysis, tax avoidance is measured through the Effective Tax Rate (ETR) and Book-Tax Differences (BTD). The results indicate that politically connected SOEs have significantly lower ETRs (β = 0.231, p < 0.01) and higher BTDs (β = 0.187, p < 0.05), confirming their tendency to engage in tax avoidance. Furthermore, government ownership negatively correlates with ETR (β = -0.256, p < 0.01), suggesting that firms with higher political influence pay lower taxes. However, the moderating role of firm profitability on the relationship between political connections and tax avoidance is not significant (p > 0.05). The fixed-effects model (Hausman test: p = 0.034) is found to be the best fit, with an R² of 67.8%, indicating that most variations in tax avoidance can be explained by the model. These findings highlight the need for stronger corporate governance and regulatory oversight to prevent excessive tax avoidance among politically affiliated firms. The study contributes to the literature on corporate tax strategies and political economy, emphasizing the importance of tax transparency and policy reforms in emerging economies.